Membangun Potensi Desa melalui Pemberdayaan Masyarakat: Studi Kasus Kampung Ciboleger, Banten - Muhaemin, Asep Mukmin; Hasanah, Tatu Raudhatul (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims to assess the significant impact of community empowerment on unleashing the village potential in Ciboleger Village, Banten. Through research methods consisting of appropriate research design, comprehensive data collection, and careful data analysis, we try to understand the impact of empowerment on village potential. The results demonstrate tangible economic improvements, empowerment of women and children, and advancements in tourism development directly resulting from the empowerment program. However, there are still obstacles and challenges such as limited resources and social change that need to be overcome. Effective strategies in improving community empowerment include establishing partnerships with local businesses for skill-building workshops and organizing community skill-sharing sessions to enhance community capacity. Through the implementation of empowerment initiatives in Ciboleger Village via religious, educational, and social programs, significant social transformations are anticipated. The conclusion of this study provides actionable recommendations, such as implementing mentorship programs for sustainable skill development and establishing micro-finance initiatives, to enhance future community empowerment programs.